2018
DOI: 10.1530/ec-18-0158
|View full text |Cite
|
Sign up to set email alerts
|

Sexual steroid hormone receptors profiles of ovarian carcinoma in Mexican women

Abstract: The significance of the presence of androgen receptor (AR), estrogen receptor alpha (ER) and progesterone receptor (PR) in ovarian cancer patient survival has been a matter of numerous studies. This study was aimed to describe the expression profile of the three sexual steroid receptors in high-grade serous, endometrioid, mucinous and low-grade serous ovarian carcinoma and its association to the proliferation index in patients with primary ovarian carcinoma diagnosis, before any treatment. Eighty-one samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…WT1 and p53 showed previous success for use in small biopsy specimens from extraovarian sites due to little variability between ovarian and omental sites 11 . In their study of sex steroid hormone receptors expressed in ovarian carcinomas, Gomora MJ 12 . However, other studies confirmed ER positivity in these tumors, associated with recurrent disease and peritoneal metastasis 13 .…”
Section: Resultsmentioning
confidence: 99%
“…WT1 and p53 showed previous success for use in small biopsy specimens from extraovarian sites due to little variability between ovarian and omental sites 11 . In their study of sex steroid hormone receptors expressed in ovarian carcinomas, Gomora MJ 12 . However, other studies confirmed ER positivity in these tumors, associated with recurrent disease and peritoneal metastasis 13 .…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have included EnOC cases when investigating the prognostic impact of hormone receptor positivity on OC outcome [[13], [14], [15], [16],[19], [20], [21], [22]]; however, the majority of these studies have included fewer than 30 EnOC cases in the context of mixed histology cohorts [[14], [15], [16],19,20]. One study collected a relatively large series of EnOCs (84 cases), but did not perform histotype-specific analysis of outcome [13].…”
Section: Introductionmentioning
confidence: 99%
“…The association of MMP-2 and MMP-9 with the expression of AR in the ovarian tumor analyzing the whole population is interesting as it provides evidence of the possible significance of the androgen receptor in ovarian tumors, being the most frequent receptor in ovarian cancer [20] associated to MMP-2 and MMP-9 which are Fig. 2 a Immunofluorescence for high grade serous carcinoma (HGSC) and endometrioid carcinoma.…”
Section: Metalloproteinases and Overall Patient Survivalmentioning
confidence: 99%
“…On the other hand, sexual steroid hormone receptors (androgen receptor -AR-, estrogen receptor alpha -ERα-, and progesterone receptor -PR-) are present in the nucleus of epithelial cells in ovarian carcinoma [19,20] and their presence has been associated with disease-free and overall survival of the patients [21,22] with their effect on tumor cell survival having been evaluated in primary cultures of epithelial ovarian tumors [23].…”
Section: Introductionmentioning
confidence: 99%